Unusual Case of Extraction of Maxillary Lateral Incisors and Mandibular Central Incisors - Rosa-María Yañez-Vico; Maria Cadenas de Llano-Perula; Enrique Solano-Reina (Case Reports in Dentistry)
Introduction. This article’s purpose is to report a case where maxillary lateral incisors and mandibular central incisors are extracted and a canine substitution was performed as the best therapeutic option in order to obtain symmetry in a malocclusion with an upper lateral incisor with poor prognostic, solve moderate crowding, get enough space for the permanent dentition, and provide stability to the results. Case Report. An 11-year-old boy with straight profile with acute-to-normal nasolabial angle and protruded lips, mixed dentition, lower and upper severe crowding, and a bilateral molar angle Class I. The left maxillary lateral incisor failed endodontic treatment secondary to an intrusive traumatic lesion in the primary and permanent dentition. The treatment of choice was the extraction of both upper lateral incisors and both central lower incisors. The patient finished with molar and canine angle Class I and coincident midlines and was functionally stable; both lateral and protrusive jaw movements were effectively made by the first premolars and central incisors and canines without improper contacts of the rest of the teeth. Overbite of one-third and correct overjet were also achieved, and the esthetic outcome was satisfactory due to the composed material restorations of both the central and lateral incisors, as well as recontouring of the first maxillary premolars.